Late Holocene sea-level changes in eastern Québec and potential drivers. (1st January 2019) - Barnett, R.L.; Bernatchez, P.; Garneau, M.; Brain, M.J.; Charman, D.J.; Stephenson, D.B.; Haley, S.; Sanderson, N.
Abstract: Late Holocene sea-level changes can be reconstructed from salt-marsh sediments with decimetre-scale precision and decadal-scale resolution. These records of relative sea-level changes comprise the net sea-level contributions from mechanisms that act across local, regional and global scales. Recent efforts help to constrain the relative significance of these mechanisms that include sediment dynamics and isostasy, which cause relative sea-level changes via vertical land motion, ocean-atmosphere processes that influence regional-scale ocean mass redistribution, and ocean-cryosphere and steric interactions that drive global scale ocean-volume changes. There remains a paucity of high-resolution Late Holocene sea-level data from eastern Canada. This precludes an interrogation of the mechanisms that define sea-level changes over recent centuries and millennia in a region sensitive to oceanic (Atlantic Multidecadal Variability, Atlantic Meridional Overturning Circulation), atmospheric (North Atlantic Oscillation, Arctic Oscillation) and cryospheric (ice-mass balance) changes. We present new relative sea-level data that span the past three millennia from Baie des Chaleurs in the Gulf of St. Lawrence generated using salt-marsh foraminifera supported with plant macrofossil analyses. The accompanying chronology is based on radiocarbon and radionuclide analyses, which are independently verified using trace metal and microcharcoal records. Relative sea level has risen at a mean rate of 0.93 ± 1.25 mm yr −1 over the past ∼1500 years. Residual structure within the reconstruction ('internal variability') has contributed up to an additional 0.61 ± 0.46 mm yr −1 of short-lived RSL rise prior to 1800 CE. Following a sea-level low stand during the Little Ice Age, acceleration in relative sea-level rise is identified between 1800 and 1900 CE within the estimates of internal variability and from 1950 CE to present in both the secular and residual trends. Phases of relative sea-level changes in the Gulf of St. Lawrence are concomitant with periods of glacier mass loss following the Little Ice Age, phase periods of the North Atlantic Oscillation and the Atlantic Meridional Overturning Circulation and Northern Hemisphere warming. Quantifying the individual effects of these different mechanisms is important for understanding how ocean-atmosphere processes redistribute ocean-mass upon larger scale background ocean-volume changes. Highlights: Late Holocene relative sea-level changes are reconstructed using foraminifera. Lowered relative sea level in eastern Canada during the Little Ice Age. Relative sea level rise (SLR) is around 1 mm.yr −1 during the Late Holocene. Internal variability can increase the rate of SLR to 2 mm.yr −1 . Recent SLR follows warming, AMOC deterioration and weakened NAO.